Isthmocele: controversial issues of terminology, diagnosis and treatment. A review - Natalia M. Podzolkova; Anton V. Demidov; Vasilii B. Osadchev; Kirill V. Babkov; Yulia V. Denisova (IP Berlin A.V., 2024)
The frequency of abdominal delivery in the world is steadily rising. Since the latter is associated with a lot of complications compared with vaginal delivery, the increase in the proportion of deliveries in women with a uterine scar through the natural birth canal is an important strategic goal of the obstetrics and gynecology community. In addition, it is established that every second patient after a cesarean section develops a defect in the scar area, which is often accompanied by various disorders of the menstrual cycle (in 25,5% of cases - abnormal uterine bleeding) and can cause secondary infertility. Both assessment of the risk of scar failure at the stage of preconceptional preparation and timely detection and treatment of isthmocele symptoms are still serious challenges facing obstetricians and gynecologists. Clinical guidelines devoted to the cesarean scar defect problem have not yet been developed. This review presents the quintessence of modern data on possible risk factors, clinical manifestations with a detailed consideration of pathophysiological mechanisms, diagnostic tools and correction methods of symptomatic isthmocele and uterine scar defect with a detailed description of indications and a comparative assessment of their effectiveness in order to standardize approaches to the diagnosis and treatment of these pathological conditions.